Importance of early diagnosis in mucoepidermoid carcinoma. Case report - Moriya Agüero, Angélica Miyuki (2023)
Mucoepidermoid carcinoma is the most frequent malignant tumor of the minor salivary glands, usually located in the palate. The objective of this case report is to demonstrate in the Paraguayan scientific literature the importance of early diagnosis of oral carcinomas as well as the fundamental role of the general dentist in identifying, guiding and referring the patient to the corresponding specialist. The clinical case presented is about a male patient who attended the Faculty of Dentistry of the National University of Asuncion. His dentist referred him after noticing a small but perceptible change in the normal coloration of the mucosa and occasional discomfort in the area of the hard palate. In the intraoral examination, an ovoid nodular lesion, purplish in color, 1cm in diameter, depressible on palpation, observed on the hard palate at the level of the premolars in the left hemiarch. An incisional biopsy performed for histopathological study, reporting a mucoepidermoid carcinoma. Regarding the early diagnosis of this type of pathology, the challenge for the general dentist will continues to be his continuous training in order to be able to successfully guide the patient in seeking care from the right specialist in case of any change in the oral cavity.